Comparative Study of Three Psycho-Socio-Educational Intervention Models to Facilitate the Comprehensive Development of Students with Autism Spectrum Disorder - Manuel Ojea Rúa (Disease and Health Research: New Insights Vol. 7, 2024)
The Psychosocial Mediation Model is not exclusive of the need for service provision, nor of the elaboration of specific programs, but it emphasizes professional and formative empowerment, in order to generate the competencies needed by teachers and families for adequately addressing students in their context, trying to provide a global response to demanding situations. This research consists of a comparative analysis of the results obtained in the development of students with autism spectrum disorders (ASD) found as a consequence of the application of three basic models of educational guidance: 1) the Psychosocial Mediation Model; 2) the Counselling Model; and 3) the Services Model, delivered through services developed over three years, distributed across three experimental groups corresponding to each of these guidance models. A total of 18 students with ASD of different levels, ages, and genders participated in the study, assigned to one of the three following groups: a social mediation model group, a counselling model group, and a services model group. A study of the data was undertaken by analysing the multivariate contrasts of repeated measures ANOVA for a factor of three measures, both for the variable group types (three groups), as well as for the participants’ level, age, and gender variables. Results show the statistically significant benefits of the social mediation model. Indeed, data found over three successive measurements indicate that in the third comparative measure, the Psychosocial Mediation Model shows comparative improvements, corroborated by significantly higher statistical means in regard to the other educational models, being mean for the Psychosocial Mediation Model (µ: 4.00), in relation to the control models, the Counselling Model (µ: 2.66) and the Services Model (µ: 2.33), whose critical values are statistically significantly different between the three models. However, when the ASD level interacts with the intervention model applied, the differences found do not show significant critical statistics, mainly in ASD level-3. The neurocognitive processing levels will affect psychosocial integral development, both the learning process itself and the development of social interaction and communication skills and the positive development of restrictive behaviours observable in people with ASD.